Primary Immunodeficiency in Children With Autoimmune Cytopenias: Retrospective 154-Patient Cohort - Westermann-Clark, Emma; Meehan, Cristina Adelia; Meyer, Anna K.; Dasso, Joseph F.; Amre, Devendra; Ellison, Maryssa; Patel, Bhumika; Betensky, Marisol; Hauk, Charles Isaac; Mayer, Jennifer; Metts, Jonathan; Leiding, Jennifer W.; et al. (Frontiers in Immunology, 2021)
Background: Primary immunodeficiency is common among patients with autoimmune cytopenia. Objective: The purpose of this study is to retrospectively identify key clinical features and biomarkers of primary immunodeficiency (PID) in pediatric patients with autoimmune cytopenias (AIC) so as to facilitate early diagnosis and targeted therapy. Methods: Electronic medical records at a pediatric tertiary care center were reviewed. We selected 154 patients with both AIC and PID (n=17), or AIC alone (n=137) for inclusion in two cohorts. Immunoglobulin levels, vaccine titers, lymphocyte subsets (T, B and NK cells), autoantibodies, clinical characteristics, and response to treatment were recorded. Results: Clinical features associated with AIC-PID included splenomegaly, short stature, and recurrent or chronic infections. PID patients were more likely to have autoimmune hemolytic anemia (AIHA) or Evans syndrome than AIC-only patients. The AIC-PID group was also distinguished by low T cells (CD3 and CD8), and low immunoglobulins (IgG and IgA). AIC diagnosis preceded PID diagnosis by 3 years on average, except among those with partial DiGeorge syndrome. AIC-PID patients were more likely to fail first-line treatment. Conclusions: AIC patients, especially those with Evans syndrome or AIHA, should be evaluated for PID. Lymphocyte subsets and immune globulins serve as a rapid screen for underlying PID. Early detection of patients with comorbid PID and AIC may improve treatment outcomes. Prospective studies are needed to confirm the diagnostic clues identified and to guide targeted therapy.